The Potential of Using Google Expeditions and Google Lens Tools under STEM-education in Ukraine - Євгеній Шаповалов; Жанна Білик; Артем Атамась; Олександр Учитель (Academy of Cognitive and Natural Sciences, 2019)
Shapovalov Yе.B., Bilyk Zh.I., Atamas A.I., Shapovalov V.V. and Uchytel A.D. The Potential of Using Google Expeditions and Google Lens Tools under STEM-education in Ukraine. The expediency of using the augmented reality in the case of using of STEM-education in Ukraine is shown. The features of the augmented reality and its classification are described. The possibilities of using the Google Expeditions and Google Lens as platforms of the augmented reality is analyzed. A comparison, analysis, synthesis, induction and deduction was carried out to study the potential of using augmented reality platforms in the educational process. Main characteristics of Google Expeditions and Google Lens are described. There determined that augmented reality tools can improve students motivation to learn and correspond to trends of STEM-education. However, there problems of using of augmented reality platforms, such as the lack of awareness of this system by teachers, the lack of guidance, the absence of the Ukrainian-language interface and responding of educational programs of the Ministry of Education and Science of Ukraine. There proposed to involve methodical and pedagogical specialists to development of methodical provision of the tools of augmented reality.